Storytelling and Creative Writing: Critical Literacy Practices in a Community Learning Center in Central Java - Sakhiyya, Zulfa; Moore, Leslie; Wardi, Tati (UIII Press, 2025)
Despite providing flexible, accessible and relevant learning opportunities to Indonesia’s marginalized groups, the equivalency program is looked down upon and its students are labelled with the stigma of second-class students. By co-constructing qualitative data through document analysis, site visits and interviews with the principal, facilitators and students of Omah Dongeng Marwah, a community learning center which provides a high school equivalency program in Kudus Central Java, the current study challenges such stereotypes by exploring critical literacies as practiced in the community learning center. This study argues that meaningful literacy practices, especially storytelling and creative writing, can be effective and viable mechanisms to enhance literacy learning, and build student agency and voice. Our findings reveal that storytelling might contribute to the improvement of reading skills as students are exposed to diverse narratives, while creative writing offers a space where students can practice articulating their ideas and feeling in authentic and meaningful ways. More importantly, storytelling and creative writing as practiced in the learning process have given underprivileged students opportunities and agency to define themselves despite being marginalized.